Development of method for quantitative determination of water arsenic by field test kit - Sekine, Makoto; Tokumura, Masahiro; Raknuzzaman, Mohammad; Ahmed, Md Kawser; Islam, M Rafiqul; Masunaga, Shigeki (Fundamental and Applied Agriculture, 2017)
Drinking of arsenic (As) contaminated ground water is threatening the health of millions of peoples of Bangladesh. The screening of tube wells (TWs) water for As in Bangladesh and elsewhere in the world is done by As testing kits. The results of water-As by these kits are semi-quantitative and personal error is high. An attempt has been undertaken for quantitative determination of water-As by MITech arsenic test kit by applying quantitative image analysis method from the digital picture of the colored test paper of the kit. In the quantitative image analysis method, the color of the test paper is numerically determined by color difference between the test water samples with the standard color chart which is calculated from Lab (lightness (L), color opponent green-red (a), and color opponent blue-yellow (b) values. TWs water-As concentrations in Bashailbogh village, Munshiganj, Bangladesh were determined by using MITech arsenic field test kit by conventional method, quantitative image analysis method and inductively coupled plasma mass spectrometer (ICP-MS) method. The water-As by the quantitative image method gave quite close results (R2 = 0.998) to those obtained with ICP-MS method at concentration up to 50 μg As L−1. The water-As concentration more than 50 μg As L−1 by this method was underestimated. Hence, the developed method may be used for quantitative analysis of water-As in the range of 0-50 μg As L−1 for water-As screening program.